2016
DOI: 10.1136/heartjnl-2015-308506
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific versus overall cut points for a high sensitivity troponin I assay in predicting 1-year outcomes in emergency patients presenting with chest pain

Abstract: ISRCTN No. 21109279, ACTRN12609000283279.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 18 publications
2
34
2
Order By: Relevance
“…Regarding the highly sensitive cTnI assay, some studies report that the use of gender specific decision values significantly increases AMI diagnosis especially in women, with better stratification of risk [112,[135][136][137], while another study found contradictory results [138]. The evidences regarding the highly sensitive cTnT assay are, on the contrary, all negative, suggesting that genderspecific clinical decision values are not particularly useful for the highly sensitive cTnT assay [117,118,139].…”
Section: Clinical Relevance Of Gender-specific Decision Values For Ctmentioning
confidence: 86%
“…Regarding the highly sensitive cTnI assay, some studies report that the use of gender specific decision values significantly increases AMI diagnosis especially in women, with better stratification of risk [112,[135][136][137], while another study found contradictory results [138]. The evidences regarding the highly sensitive cTnT assay are, on the contrary, all negative, suggesting that genderspecific clinical decision values are not particularly useful for the highly sensitive cTnT assay [117,118,139].…”
Section: Clinical Relevance Of Gender-specific Decision Values For Ctmentioning
confidence: 86%
“…Shah et al (11 ) argue that the use of a single diagnostic threshold has disproportionately disadvantaged women and contributed to underdiagnosis of female AMI. Cullen and colleagues have recently shown that sex-specific cutoffs improve the identification of major cardiovascular event outcomes in women at 1 year (14 ). Our data show that there was no follow-on effect from increased cardiac troponin to angiography rates.…”
Section: Discussionmentioning
confidence: 43%
“…Application of sex-specific 99th percentile values (4 ) was reported to increase numbers of non-ST elevation myocardial infarctions (NSTEMIs) by 4.7%-11% in females depending on the hs-cardiac troponin assay used, but also to decrease numbers of NSTEMIs in males by 2%-3% (5-7 ). Whether diagnostic reclassification translates into improved prediction of outcomes is a matter of controversy with some studies reporting an unequivocal benefit (5 ) in contrast with others reporting no (6 -8 ) or only a little clinical impact (9 ). In a retrospective register-based study on 48250 patients, Eggers et al (6 ) found no evidence for a better risk prediction using sex-specific 99th percentiles.…”
mentioning
confidence: 92%
“…Interestingly, better outcome prediction was found at cutoffs substantially lower than the 99th percentile values (Ն6 ng/L for women and Ն7 ng/L for men using ROC analyses, and Ն6 ng/L for women and Ն9 ng/L for men using logistic regression modeling). Therefore, Cullen et al (9 ) recommended consideration of lowering the clinical cutoff for both sexes for prognostic purposes instead of using sexspecific 99th percentile values as recommended by the manufacturer. Consistent with this, the optimal cutoffs for a rapid 1-h NSTEMI rule-out and rule-in algorithm in suspected ACS were determined as Ͻ5 and Յ6 ng/L, respectively with the use of the same STAT Architect hs-cTnI assay in 2 other large ACS cohorts (10 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation